ECONOMIC VALUATION OF ECOSYSTEM SERVICES IN DIMBHERESERVOIR, MAHARASHTRA - SNEHA DADARO, WAGHMARE; YADAV, VINOD KUMAR; MEHAROOF, MOHAMMED; RAMTEKE, KARANKUMAR KUMAR; PANDIT, ARUN; SHARMA, ARPITA (Journal of the Inland Fisheries Society of India, 2024)
Reservoirs provide a range of ecological and economic services to human beings which are referred to as “ecosystem services”. This study focuses on identifying and determining the value of ecosystem services provided by Dimbhe Reservoir in Maharashtra, India, to highlight the importance of preserving and managing this valuable resource. Primary data from 160 households were collected and single and double bounded Contingent Valuation Method (CVM) were used to find the willingness to pay of respondents. In CVM, the logistic model was used based on the dichotomous choice method to randomly estimate the WTP with three different bid values (first bid, low bid, and high bid, which were 250, 100, and more than 250, respectively). The study estimated the economic value of six provisional services viz. employment, water for irrigation, water for drinking, hydroelectric power generation, fuel wood, and fishing in the reservoir. The average total economic value of provisioning services in the Dimbhe reservoir was estimated as 899.6 lakhs per year. Education, house type, and monthly household income were the significant potential factors for WTP for the provisioning services.